Tax Havens, offshore wealth and tax evasion. An estimate for Spain (1980-2013) - Peramo, Juan Carlos (Papeles de Europa, 2016)
The problematic of tax havens is an increasingly relevant phenomenon in the functioning of the world economy and is closely related to the financial crisis and rising inequality. However, there is little literature to quantify the problem. The purpose of this work is to develop a methodology as a basis for extending the study of this subject, so little studied and still too unknown, despite its importance and presence nowadays. For this, the terminology used in the literature on tax havens and offshore wealth as well as the methodology used in some estimates that quantify the problem is collected. From this collection an estimate for Spain is proposed for the 1980-2013 period, wealth based in tax havens (offshore) and its impact on tax revenues, applied by Zucman to the case of France. The results show an increase in offshore wealth throughout the period and a loss of tax revenue accumulated for the country of 116.000 million euros.